Pivoting to Inclusion : Leveraging Lessons from the COVID-19 Crisis for Learners with Disabilities - World Bank (World Bank, Washington, DC, 2020)
As governments respond to the Coronavirus 2019 (COVID-19) pandemic, the global community must ensure that persons with disabilities are included. This will require disability inclusion to be considered in all interconnected sectors; education, health, social protection, and inclusion from the planning stage all the way through to delivery and recovery efforts that are inclusive of all and are sufficiently differentiated to meet the specific needs of children with disabilities. The issues paper focuses on the following objectives: (1) addressing education, social needs, barriers, and issues for learners with disabilities at a global, regional, and country-level during the COVID-19 crisis; and (2) recommending practices for education and social inclusion, and reasonable accommodations utilizing the twin track approach and principles of universal design for learning.